In Vitro Callogenesis In Bryonopsis Laciniosa (L). Naud - V.J.E CAROLINE; S. MADHAVI; B.MALLAIAH (International Journal of Pharma and Bio Sciences, 2012)
Bryonopsis laciniosa (L.) Naud is an endangered and valuable medicinal plant belongs to the family Cucurbitaceae. It is commonly known as lollipop climber and is globally distributed in the paleotropics. Bryonopsis plants are used to treat various types of diseases. Different explants like leaf, cotyledon, nodal, stem and branch segments were tested on MS medium supplemented with different concentrations of 2, 4 – D, BAP, IBA, NAA, TDZ and L – glutamic acid. Excess of callus growth occurred in nodal explants on MS medium fortified with 2.0 mg/l 2, 4 – D and 5.0 mg/l BAP. It was observed that among the explants tested nodal, cotyledon and stem explants were key material for excellent callus proliferation and growth.